PERANAN TANAMAN PENGHIJAUAN ANGSANA, BUNGUR, DAN DAUN KUPU-KUPU SEBAGAI PENYERAP EMISI PB DAN DEBU KENDARAAN BERMOTOR DI JALAN COKROAMINOTO, MELATI, DAN CUT NYAK DIEN DI KOTA DENPASAR - Luh Komang Sulasmini; M.S. Mahendra; Komang Arthawa Lila (Master Program of Environmental Science, Postgraduate Program of Udayana University)
The aim of this study was to observe the role of green trees to air quality in Denpasar City. Theresearch locations were at Cokroaminoto, Melati, and Cut Nyak Dien streets, during February 2006 to July2006. The sample plants were: angsanas, timber, and purple orchid leaf. Statistical analysis was conductedby applying double linier regression and anova test.The result showed that the highest total vehicle number (11.573 and 3.330), noise level (72,75 dB),air Pb concentration (0,313 ?g/m3), concentration of particulates (244 ?g/m3), temperature humidity index(27,45), wind speed (1,44 m/second), humidity (70,77 %), type and number of trees were observed atCokroaminoto street (26 types and 866 trees), whilst the lowest values were at Cut Nyak Dien street (7 typesand 121 trees). The highest temperature was observed at Melati street (29,25 oC) and the lowest was at Cut Nyak Dien street (28,51 oC). From the three places observed, the highest number of trees, height of tree, andwidth of crown were on angsanas tree (439 trees; 7,07 m; dan 8,7 m) and the lowest value was calculatedon purple orchid leaf (14 trees; 4,60 m; dan 5,8 m). On the other hand the highest leaf wide was on timber(131,550 cm2) and the lowest on angsanas (42,745 cm2). Concentrations of Pb leaves were calculated asfollows: angsanas 13,228 mg/kg; timber 13,208 mg/kg; purple orchid leaf 12,897 mg/kg, respectively.Statistical result showed that total plants, total motor cycle and total four wheels vehicles was notpartially or simultaneously affected air Pb and air dirt concentrations. Height of tree, width of leaves andwidth of crown did not affect leaves Pb concentration both partially and totally to leaves Pb. Based onlocation, it can be concluded that there was no difference of air dirt and air Pb concentration, but there isdifference in leaves Pb. Based on type of trees there was no significant difference on leaves Pb contentamong trees type, it means that every tree has similar ability in absorbing Pb.